Ability to adopt office of godfather in the Latin Church - JAKUBIAK, TOMASZ (Prawo Kanoniczne, 2017)
The mission of godfather is an ecclesial office (ecclesiale officium) and as such may be entrusted to one who is fit, that is possess required qualities (see can. 149§1 CIC). Conditions to be met by candidates for godparents so they can be admitted to this ecclesiastical officium, were included in the can. 874§1 CIC. Establishing criteria that should be followed when choosing godparents, the legislator is trying to protect against unwise or even fictional entrusting the office to a person who is not able to fulfill the tasks incumbent on the godparents at the moment of baptism and in the future. In connection with the emerging doubts about the implementation of the standard saved in the can. 874§1CIC, author decided to herein bring its interpretation. This is all the more useful since the complexity of life situations poses difficulties to pastors when deciding on admitting or not admitting people to take the office of godparent. Admitting a person to undertake the task godfather is not only dependent on its suitability. Restrictions may be the result of other rules regulating the life of the Latin Church, which are also quoted by the author.